PERAN AKTIF WANITA PEMECAH BATU DALAM MEMBANTU PEREKONOMIAN KELUARGA DI DUSUN SEMAYA DESA PRINGGABAYA UTARA LOMBOK TIMUR - Sahar Sahar (Fakultas Ekonomi Universitas Islam Al-Azhar, 2020)
This study aims to determine the role of what is done by stone-breaking women in helping the family economy in Semaya Hamlet, Pringgabaya Utara Village, East Lombok. This study discusses the role of women in helping the family economy seen from the economic and non-economic roles in supporting its role.The study used a qualitative fenomenologi approach. The subjects of the study were stone-breaking female workers. Data collection using observation, interviews and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. Triangulation used is triangulation of sources and techniques.The results of this study indicate the role of women in helping the family economy in Semaya Hamlet, Pringgabaya Utara Village, East Lombok, both directly and indirectly the role of women is very strong, the spirit of women working is very large even though with a small income women have taken part in helping the family economy by doing work in the public sector to help her husband. With the workings of the wife automatically her role becomes double, namely to become a housewife and as a working wife.